COMPARATIVE STUDY ON THE IMMEDIATE EFFECTS OF DEEP BREATHING EXERCISES WITH PEP DEVICE VERSES INCENTIVE SPIROMETRY WITH EPAP ON PREVENTING PULMONARY COMPLICATIONS FOLLOWING CABG (International Journal of Physiotherapy, 2016)
Background: The initial days following CABG is a crucial period as it imposes a high risk of pulmonary complications and morbidity. In an effort to increase lung volume following surgery, various deep breathing manoeuvres have been implemented as a main component in the care of the postoperative patient. The rationale for Deep Breathing Exercises with PEP and Incentive Spirometry is that they prevent postoperative complications (PPC), thereby improving cardiorespiratory function. Various studies to substantiate the effectiveness of Deep Breathing Exercises with PEP devices and Incentive Spirometry on preventing pulmonary complications following CABG surgery have been done. The need to study immediate effects of both techniques is yet to be studied.Methods: 30 subjects undergoing CABG and fulfilling the inclusion criteria were selected for the study. They were randomly assigned into two groups: Group A and Group B having 15 subjects each. Group A received Deep Breathing Exercises with a positive expiratory pressure (PEP) device and Group B received Incentive Spirometry with Expiratory Positive Airway Pressure (EPAP).Results: The value of F = 45.729 to find the difference in PEFR in Group B is significant (p=0.00). It has been found that PEFR increased significantly after application of incentive spirometer with EPAP to the patients after 4th day. On Day 4, t = 3.750, which is significant (p = 0.001) implying that deep breathing exercise with PEP device is more effective to increase PEFR as compared to incentive spirometer with EPAP.Conclusion: PEP device is more effective than Incentive Spirometry with EPAP in preventing postoperative complications following CABG surgery. It can be inferred that deep breathing exercise with PEP device is more effective than incentive spirometer with EPAP in improving SPO2 and PEFR in both the groups.